1997
DOI: 10.1093/oxfordjournals.aje.a009122
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific Incidence Rates of Myocardial Infarction and Angina in Women with Systemic Lupus Erythematosus: Comparison with the Framingham Study

Abstract: The authors ascertained cardiovascular events (myocardial infarction and angina pectoris) in 498 women with systemic lupus erythematosus seen at the University of Pittsburgh Medical Center from 1980 to 1993 (3,522 person-years). Subjects were stratified by age, and cardiovascular event incidence rates were determined. The authors compared these rates with cardiovascular event rates were determined. The authors compared these rates with cardiovascular event rates occurring over the same time period in 2,208 wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

48
1,151
9
59

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,628 publications
(1,267 citation statements)
references
References 30 publications
48
1,151
9
59
Order By: Relevance
“…In conclusion, since women with SLE are at an increased risk of developing premature menopause (2), osteoporotic fractures (44), cognitive dysfunction (45), premature atherosclerosis (46), thrombosis (40), and cardiovascular events (47), and their quality of life often is poorer than that of the general population (48), the effects of menopause in addition to these conditions, and the risk-benefit profile of menopause hormonal therapy in these women and those with other chronic diseases, need to be explored in depth. Menopause hormonal therapy did not affect the course of disease activity, at a clinically significant level, in women with SLE who were in the menopausal transition or in early or late postmenopause.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, since women with SLE are at an increased risk of developing premature menopause (2), osteoporotic fractures (44), cognitive dysfunction (45), premature atherosclerosis (46), thrombosis (40), and cardiovascular events (47), and their quality of life often is poorer than that of the general population (48), the effects of menopause in addition to these conditions, and the risk-benefit profile of menopause hormonal therapy in these women and those with other chronic diseases, need to be explored in depth. Menopause hormonal therapy did not affect the course of disease activity, at a clinically significant level, in women with SLE who were in the menopausal transition or in early or late postmenopause.…”
Section: Discussionmentioning
confidence: 99%
“…The risk appears to accumulate over time and persists after adjustment for other cardiovascular risk factors (relative risk of MI is greater than three after 10 years of having the disease) [6,12] suggesting that RA independently doubles the hazard for myocardial infarction and sudden cardiac death. The degree of increased risk of myocardial infarction in SLE patients varies, with risks as high as 50-fold in premenopausal women and decreasing to the risk of the general population in the elderly [13][14][15]. The nurses' health study found a slightly greater than twofold risk of cardiovascular disease in lupus patients [16].…”
Section: Introductionmentioning
confidence: 99%
“…The estimated 5-year risk of arterial thrombosis ranges from 5.1% to 8.5%, while 5-year venous thrombosis risk ranges from 3.7% to 10.3% (1). Consequently, patients with SLE have a significantly increased risk of premature cerebrovascular accident (CVA) and myocardial infarction (MI) compared with agematched controls (2)(3)(4)(5). Although most studies document a role of traditional cardiovascular risk factors, the increased incidence of cardiovascular disease in SLE cannot be explained by traditional risk factors alone, suggesting that there are additional factors contributing to atherothrombotic disease in SLE (3,4,6 -8).…”
Section: Introductionmentioning
confidence: 99%